Inkulturasi dalam Pertunjukan Wayang Wahyu: Katekese Iman Melalui Seni - Faisal, Stephanus Agus; Wahyudi, Rifqi; Dwi Setiawan, Edwin Wahyu (Fakultas Teologi, Universitas Sanata Dharma, 2024)
After the Second Vatican Council, the Church showed an open attitude towards local cultural influences as an integral part of its pastoral mission. In Indonesia, the Church responded to this current by adopting various forms of inculturation that went beyond ritual and worship aspects. Br. L. Timotius Wignyosubroto, FIC, responded to this challenge by developing the concept of Wayang Wahyu as an innovative means of faith catechesis through art. Through the establishment of the Ngajab Rahayu group in Surakarta, Wayang Wahyu became a medium that combines elements of traditional Wayang Kulit art with biblical narratives from the Old and New Testaments, as well as religious figures such as the founder of the Order and saints. In every Wayang Wahyu performance, theological dimensions are manifested, such as the Trinity, Christology, Pneumatology, Ecclesiology, and Anthropology. Wayang Wahyu is not just a performing art, but also a creative instrument to instill Christian values and deepen faith catechesis in the local cultural context.AbstrakPasca Konsili Vatikan II, Gereja menunjukkan sikap terbuka terhadap pengaruh budaya lokal sebagai bagian integral dari misi pastoralnya. Di Indonesia, Gereja merespon arus ini dengan mengadopsi berbagai bentuk inkulturasi yang melampaui aspek ritual dan peribadatan. Br. L. Timotius Wignyosubroto, FIC, merespons tantangan ini dengan mengembangkan konsep Wayang Wahyu sebagai sarana inovatif katekese iman melalui seni. Melalui pendirian kelompok Ngajab Rahayu di Surakarta, Wayang Wahyu menjadi medium yang menggabungkan unsur seni tradisional Wayang Kulit dengan narasi Alkitab dari Perjanjian Lama dan Baru, serta tokoh-tokoh keagamaan seperti pendiri Tarekat dan santo-santa. Dalam setiap pertunjukan Wayang Wahyu, terwujud dimensi-dimensi teologis, seperti Trinitas, Kristologi, Pneumatologi, Eklesiologi, dan Antropologi. Wayang Wahyu bukan hanya sekadar seni pertunjukan, tetapi juga menjadi instrumen kreatif untuk menanamkan nilai-nilai Kristen dan memperdalam katekese iman dalam konteks budaya lokal